2017
DOI: 10.1039/c7ob01385j
|View full text |Cite
|
Sign up to set email alerts
|

Catching the chloride: searching for non-Hofmeister selectivity behavior in systematically varied polyamide macrocyclic receptors

Abstract: The binding selectivity of structurally simple anion receptors is governed by the Hofmeister series (SO > HPO > carboxylates ∼ HPO > HCO > Cl), and exceptions to this rule are rare and require utilization of structurally sophisticated receptors. In this paper we examined a set of 48 structurally diverse anion receptors, barely one fourth of which exhibit selectivity for chloride over more basic dihydrogen phosphate (HPO) or carboxylates (MeCO and PhCO). Searching for regularities in the properties of these mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 77 publications
0
33
0
Order By: Relevance
“…[26] In our case the presence of anthracene groups results in equalization of association constants. Quite interestingly, host 10 exhibits similar affinity for chloride and benzoate.…”
Section: Resultsmentioning
confidence: 62%
“…[26] In our case the presence of anthracene groups results in equalization of association constants. Quite interestingly, host 10 exhibits similar affinity for chloride and benzoate.…”
Section: Resultsmentioning
confidence: 62%
“…With receptors 1 – 5 in hand, we commenced a detailed analysis of their structural properties as well as their selectivity and affinity for anion binding. We used the Cl − anion as the model target anion due to its aforementioned significance and its recurrent relatively low affinity and selectivity for neutral receptors . First, we investigated the conformational properties of the free receptors and of their Cl − anion complexes by using X‐ray crystallography.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the crystal structure of the chloride complex of receptor 4 suggests that the 20‐membered macro‐ring, previously identified as optimal for macrocyclic tetra‐amide receptors, is slightly too large to accommodate precisely small chloride anions. Studies in solution showed that all the receptors 1 – 5 have high affinities for binding to anions of different sizes and geometries (H 2 PO 4 − , carboxylates, Cl − , Br − ), even in highly competitive polar solvent media (DMSO/25 % MeOH). This confirms the privileged properties of the azulene‐based building blocks and of the macrocyclic topology for the construction of anion receptors. The relative selectivity of the binding of different anions shows that receptors containing azulene‐1,3‐bisamide building blocks display high selectivity, with an unusually high affinity for H 2 PO 4 − , in line with both the Hofmeister trend and previous findings; however, receptors containing the azulene‐5,7‐bisamide building block display a higher affinity for commonly weakly binding Cl − over the carboxylates PhCO 2 − and MeCO 2 − , which are typically strongly interacting anions. This shows that the usual selectivity of anion binding of the Hofmeister series can be overturned by making adjustments to the geometry of the binding site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations